Effects of physical activity and sleep duration on fertility: A systematic review and meta-analysis based on prospective cohort studies - Zhao, Fanqi; Hong, Xiang; Wang, Wei; Wu, Jingying; Wang, Bei (Frontiers in Public Health, 2022)
Objective: Subfertility is a common problem for couples in modern society. Many studies have confirmed that lifestyle factors can affect fertility although there are conflicting conclusions relating to the effects of physical activity and sleep duration on fertility. In this study, we aimed to summarize and analyze the available evidence. Methods: PubMed, Web of Science, Cochrane, and Embase databases (as of October 14, 2022) were systematically searched for eligible prospective cohort studies. Data were extracted and effect values were combined. We also performed methodological quality and bias risk assessments for all the included studies. Results: A total of 10 eligible articles were included in our analysis; seven investigated the relationship between physical activity and fertility, and three investigated the effect of sleep duration on fertility. Compared with the lowest level of physical activity, high intensity physical activity (the highest levels of physical activity) was negatively correlated with fertility [odds ratio (OR)=0.84; 95% confidence interval (CI): 0.70, 1.00, I^2=64%]. However, we did not find an association between moderate intensity physical activity and fertility (OR=1.09; 95% CI: 0.98, 1.22, I^2=60%). We observed an inverse association between limited sleep duration (≤ 7 hours) and fertility (OR=0.92; 95% CI: 0.84, 1.00, I^2=0%) compared with eight hours of sleep. The relationship between long sleep duration (≥ 9 hours) and fertility was not statistically significant (OR=0.85; 95% CI: 0.60, 1.21, I^2=83%). According to the Newcastle-Ottawa Scale score, the overall quality of the research articles included was ranked as medium to high (6-9). Through GRADE system, the quality of evidence for the impact of high intensity physical activity and limited sleep duration on fertility was moderate, while the quality of evidence for the impact of moderate intensity physical activity and long sleep duration on fertility was low. Conclusion: The current evidence shows that high intensity physical activity and limited sleep time are negatively related to fertility. But there was great heterogeneity among studies, and the quality of research evidence was low to median. Thus, further high-quality research is needed to confirm this conclusion.